Standing at the Intersection of Health Communication and Computational Communication: Exclusive Interview with Prof. Jingbo Meng (The Journal of Medicine, Humanity and Media, 2025)
Professor Meng Jingbo is a 2006 graduate of the School of Journalism and Communication at Peking University and holds a doctoral degree from the University of Southern California. She currently serves as an Associate Professor at the School of Communication of The Ohio State University. During the MHM 2025 Conference, we invited Professor Meng to share her experiences and insights with us.
Keywords: Health communication; Computational Communication; Artificial Intelligence